Covid-19 Health Protocol Education for Health Cadres and the Community - Sudirman; Sitti Fajrah; Rikwan (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
In 2019, the government has taken policies as an effort to optimally handle the Covid-19 storm so that it does not spread widely. The pattern of transmission of the Covid-19 virus can be through the air and can be transmitted if health protocols are not carried out properly. The level of incidence of Covid-19 has become a major problem for all communities in various regions in Indonesia, including in the Parigi area of Parigi Moutong Regency. In the last week, it was discovered that a new variant of Covid-19, the